A comparison of blood pressure indices as predictors of all-cause mortality among middle-aged men and women during 701, 707 person-years of follow-up. (October 2018) - Rosenblad, Andreas
Abstract High systolic blood pressure (SBP) is often used as a measure of hypertension in epidemiological studies. Alternative blood pressure (BP) indices include diastolic blood pressure (DBP), pulse pressure (PP), mid-blood pressure (MBP) and mean arterial pressure (MAP). The present study compares the predictive ability for all-cause mortality (ACM) of these indices and the novel BP index mean proportional arterial pressure (MPAP), defined as the weighted mean of SBP and DBP where the weights are proportional to SBP's and DBP's contributions to the sum of SBP and DBP. Using a Swedish cohort of 32, 238 middle-aged men and women, not being on antihypertensive treatment, examined in 1989–2000 and followed-up until March 9, 2017, the predictive abilities for ACM of SBP, DBP, PP, MBP, MAP and MPAP were compared using a likelihood-basedR 2 -type measure for adjusted and unadjusted Cox regression models. Of the included participants (mean age 45.4 years, 48.2% men), 2936 (9.1%) died during a mean follow-up time of 21.8 years, equalling 701, 707 person-years at risk. Higher BP were for all indices significantly associated with increased ACM. For all models, those including MPAP had the highest predictive ability, followed in turn by models including MBP, SBP, MAP, DBP and PP, respectively. The difference was significant for SBP, DBP and PP in unadjusted models and for PP in fully adjusted models. In conclusion, MPAP and MBP are the best predictors of ACM. Until the clinical usefulness of these indices has been evaluated, they may primarily be useful for epidemiological studies.